Mechano-active biomaterials for tissue repair and regeneration - Yang, Lei (Henry Stewart Talks, 2023)
Tissue repair and regeneration, Filopodial growth dynamics, Mechano-active biomaterials, Myocardial Infarction treatment, Gel-point adhesive patch (GPAP), Disordered topography, Finite-element modeling, Mediated osteoblast migration and differentiation, Diamond coating morphology, In vivo verification, Viscoelastic adhesive epicardial patch